Ethnocentrism effects on consumers' behavior during COVID-19 pandemic - Giuseppina Migliore; Giuseppina Rizzo; Giorgio Schifani; Giuseppe Quatrosi; Luigi Vetri; Riccardo Testa (Economies, 2021)
The COVID-19 pandemic has upset everyone's normal daily activities, generating psychiatric disorders and changing consumers' preferences. Among others, the agri-food sector has experienced strong changes and, during the lockdown period, Italian consumers modified their purchasing habits in response to the fear and uncertainty generated by the spread of the virus. In order to find out the main consequences of the shock suffered during the period and to understand which factors have affected purchasing choices, an online survey was conducted on 286 Italian consumers. The results show that ethnocentrism has been the factor that most has influenced consumers' behavior during the lockdown period and that consumers will continue to prefer national agri-food products when pandemic will be over, constituting a deep change to future eating habits.
Keywords: 330; agri-food products; Italian consumers; lockdown; neuropsychological effects